1978
DOI: 10.1002/gj.3350130104
|View full text |Cite
|
Sign up to set email alerts
|

Meander development and floodplain sedimentation: A case study from mid‐Wales

Abstract: Spatial and temporal patterns of meander development and sedimentation are assessed for a meander loop on the River Rheidol. Several scales and rates of change are distinguished for which different observational approaches are helpful. The meander loop itself developed over approximately 100 years while primary high-flow bedforms grew and migrated within the loop modifyingits form. These were themselves variously dissected and embellished at intermediate discharges, but their residues are preserved as a major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 9 publications
2
41
0
1
Order By: Relevance
“…Inner bank retreat has been noted in other studies (Lewin, 1978;Page and Nanson, 1982;Andrle, 1994), although these studies do not document changes in the bed topography. From the evidence presented here, it appears to be the modi®cation of the bed topography in this region that allows extensive¯ow separation to develop at the outer bank, whilst the retreat of the bank leads to widening and¯ow expansion.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Inner bank retreat has been noted in other studies (Lewin, 1978;Page and Nanson, 1982;Andrle, 1994), although these studies do not document changes in the bed topography. From the evidence presented here, it appears to be the modi®cation of the bed topography in this region that allows extensive¯ow separation to develop at the outer bank, whilst the retreat of the bank leads to widening and¯ow expansion.…”
Section: Discussionmentioning
confidence: 87%
“…Hickin (1977) and Page and Nanson (1982) proposed that channel widening at the apex of a sharply curving bend facilitates¯ow expansion and allows separation to develop at the concave bank. The work of Page and Nanson (1982), Lewin (1978) and Andrle (1994) demonstrated that it is erosion at the inner bank of the sharp bend that leads to widening. As these studies were based on observations of bend planform, the in¯uence on¯ow separation of the three-dimensional bed topography in the bends is unknown.…”
mentioning
confidence: 96%
“…Concave bank benches have been observed on tight bends on the Missippippi River (Carey, 1969), rivers in New South Wales (Nanson and Page, 1983;Woodyer, 1975), Canada (Hickin, 1979) and Wales (Lewin, 1978). Skewed meander forms have also been noted as being typical of meandering rivers by Parker et al (1989), and Lapointe and Carson (1986).…”
Section: Introductionmentioning
confidence: 86%
“…7 (Braudrick, 2013). The migration rate data was collected from the literature including previous compilations where the channel width and grain size of the bed was known (e.g., Hickin and Nanson, 1984;MacDonald et al, 1991) as well as migration studies on individual rivers (e.g., Lewin, 1978;Micheli et al, 2004;Lauer and Parker, 2008), with most of the migration data obtained from comparing aerial photographs. The individual rivers and their morphology are given in Braudrick (2013), and the channels represent a large range in channel size and discharge.…”
Section: 'Loose' Time-scaling By Bend Migration Ratementioning
confidence: 99%